2021
DOI: 10.1177/1747021821991767
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of object-based attentional selection by facial expressions

Abstract: Human beings can show preferentially attentional bias to different facial expressions. However, it is unclear whether the modulation of selective attention by facial expressions is based on the face itself (object-based attention) or its location (space-based attention). The current study aimed to test this problem by using faces with different emotional valences in the two-rectangle paradigm across three experiments. We found that there was no significant difference in space-based effect among the positive, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The results obtained in Experiment 1 revealed that both animate and inanimate objects can elicit object-based effects. This was in line with the interpretation that animate and inanimate objects can also establish strong object representation, which was the determining factor to induce object-based attention (e.g., Hu, Liu, Song et al, 2021; Shomstein & Behrmann, 2008; Zhao et al, 2015). However, previous studies have found that dangerous animals can capture and hold attention (e.g., Bugaiska et al, 2018; Lipp & Waters, 2007; LoBue, 2010).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The results obtained in Experiment 1 revealed that both animate and inanimate objects can elicit object-based effects. This was in line with the interpretation that animate and inanimate objects can also establish strong object representation, which was the determining factor to induce object-based attention (e.g., Hu, Liu, Song et al, 2021; Shomstein & Behrmann, 2008; Zhao et al, 2015). However, previous studies have found that dangerous animals can capture and hold attention (e.g., Bugaiska et al, 2018; Lipp & Waters, 2007; LoBue, 2010).…”
Section: Resultssupporting
confidence: 88%
“…The results of the present study demonstrate that neutral animate and inanimate objects could elicit object-based attention as other real objects. Regardless of whether the objects are animate or inanimate, they can elicit object-based attention similar to other real objects (e.g., Hollingworth et al, 2012; Hu, Liu, Song et al, 2021; Hu et al, 2021; Malcolm & Shomstein, 2015; Scotti et al, 2016; Zhao et al, 2020). For instance, Zhao et al (2020) investigated object-based attention by using monetary objects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al ( 2021 ) and Song et al ( 2021 ) found significant OBA effects in faces when focusing on the role of facial expressions and eye gaze. They reached the conclusion that facial expressions and eye gaze can modulate the magnitude of the OBA effect.…”
Section: Introductionmentioning
confidence: 98%
“…In these studies, the two rectangles were replaced by two human faces and the OBA effect was measured by the difference between the within and between conditions. However, these studies encountered challenges in reliably demonstrating the OBA effect with human faces (e.g., Valenza & Calignano, 2021 ; Valenza et al, 2014 ; Xie et al, 2022 ; but see Hu et al, 2021 ; Song et al, 2021 ; Yan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%